Relationship between motor dysfunction and chewing movement in patients with Parkinson's disease: A transversal study - Sano, Taisei; Umemoto, George; Fujioka, Shinsuke; Iwashita, Yuki; Dotsu, Yuriko; Wada, Naohisa; Tsuboi, Yoshio (Frontiers in Neurology, 2022)
Objective To assess the impact of chewing movement in patients with Parkinson's disease (PD), we examined the relation between chewing movement and motor dysfunction in association with PD progression. Methods Thirty patients with PD (mean age, 68.9 ± 9.0 years; mean Hoehn and Yahr stage, 3.0 ± 0.7) were recruited. The PD condition was assessed in each patient by using the score of Movement Disorder Society Unified PD Rating Scale (MDS-UPDRS) part III score, body mass index (BMI), serum albumin (Alb), and tongue pressure, number of chews, mealtime, and chewing speed were collected. The patients were divided into two groups (mild and moderate PD groups) based on an MDS-UPDRS part III cut-off value of 32. Results The chewing speed positively correlated with tongue pressure (rho = 0.69, p < 0.01) in the mild group, and with BMI (rho = 0.54, p = 0.03), serum Alb (rho = 0.63, p = 0.02), and number of chews (rho = 0.69, p < 0.01) in the moderate group. The MDS-UPDRS part III scores for all participants correlated negatively with chewing speed (rho = −0.48, p < 0.01), serum Alb (rho = −0.49, p < 0.01), and positively with mealtime (rho = 0.43, p = 0.01). Tongue pressure and serum Alb were identified to be as factors affecting the chewing speed (β= 0.560, p < 0.01; β= 0.457, p < 0.01, respectively). Conclusions These results indicated that the progression of motor dysfunction in patients with PD is likely to affect chewing speed and the nutritional status decline may be linked to the impairment of chewing movement in these patients.